Federal Practitioner 2021
DOI: 10.12788/fp.0126
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Process for Inpatient Hematology and Oncology Using Plan-Do-Study-Act Methodology Improves Follow-Up and Patient Hand-Off

Abstract: Background: Hematology and oncology patients represent a complex population that requires timely follow-up to prevent clinical decompensation and delays in treatment. Previous reports have demonstrated that follow-up within 14 days is associated with decreased 30-day readmissions, and the magnitude of this effect is greater for higher-risk patients. This project was designed to standardize the discharge process with the primary goal of reducing average time to hematology and oncology follow-up to < 14 days.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This nding might be related to the implementation of standardized care pathways that include discharge planning and better follow-up protocols. 49,50 Previous studies have found opioid dose to be associated with increased risk of long-term opioid use and its associated adverse events [51][52][53] While our ndings showed that initial doses of dispensed opioids did not exceed recommended thresholds and did not lead to increased risk of FED 54 , a longer follow-up window may be needed to accurately re ect the role of opioid dose on the risk of FED use. Over time patients may add several medications to maximize pain control, accumulating longer use over time [55][56][57] , which could consequently result in increased risk of opioid-related morbidity and healthcare utilization.…”
Section: Discussionmentioning
confidence: 56%
“…This nding might be related to the implementation of standardized care pathways that include discharge planning and better follow-up protocols. 49,50 Previous studies have found opioid dose to be associated with increased risk of long-term opioid use and its associated adverse events [51][52][53] While our ndings showed that initial doses of dispensed opioids did not exceed recommended thresholds and did not lead to increased risk of FED 54 , a longer follow-up window may be needed to accurately re ect the role of opioid dose on the risk of FED use. Over time patients may add several medications to maximize pain control, accumulating longer use over time [55][56][57] , which could consequently result in increased risk of opioid-related morbidity and healthcare utilization.…”
Section: Discussionmentioning
confidence: 56%
“…For example, we found that the receipt of any type of surgery, was associated with a decreased risk of FED use. This finding might be related to the implementation of standardized care pathways that include discharge planning and better follow-up protocols [ 52 , 53 ]. However, this finding may be a reflection of having patients in the study cohort that are at an early stage of their cancer disease and, thus, excluding the sickest population; the results should be replicated, in addition to investigating the effect measure modification of having surgery on the risk of FED, using larger cohorts within existent databases that link clinical information to administrative databases.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a scheduled follow-up appointment can lead to various adverse consequences, underscoring the importance of post-discharge care coordination in oncology settings. Such deviations have the potential to cause treatment delays, thereby impacting the patient’s well-being [ 6 ]. Failure to conduct early medical evaluations and make necessary adjustments is associated with an increased risk of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to conduct early medical evaluations and make necessary adjustments is associated with an increased risk of disease progression. Non-compliance with the prescribed follow-up schedule may result in deviations from the established treatment plan, potentially compromising its efficacy [ 7 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation